Characteristics and Biological Properties of Imeglimin Hydrochlo ride, A Novel Antidiabetic Agent: A Systematic Review - Sultan, Jasira; Agarwal, Nikhil; Sharma, Sanjay (Current Diabetes Reviews, 2024)
Background: WHO indicates that diabetes will become the 7th leading reason for death by 2030. The physiopathology of dysfunctioning is associated with obesity, weight gain and predominantly insulin resistance in insulin-sensitive cells and continuous deterioration of pancreatic beta cell function. Imeglimin is an investigational novel oral anti-diabetic drug. Objectives: The motive of the review is to comprehensively explore the chemistry, biological and analytical analysis of the Imeglimin hydrochloride. Methods: To enhance the understanding, a systematic review was conducted by forming a database of relevant existing studies from electronic resources like Web of Science, ScienceDirect and PubMed. The methodology is reflected in the PRISMA design. Result: The drug was approved in the year 2021 for therapeutic purposes in Japan. It is the novel and first approved drug for this type of Anti-diabetic treatment. It is a small molecular drug whose molecular weight is 191.6 grams per mole utilized for oral administration. Imeglimin is thought to have both activities, as the amount of glucose is dependent on insulin secretory impact and insulin sensitivity is increased. Conclusion: Therapeutic, pharmacological, and analytical considerations for the novel drug Imeglimin hydrochloride are discussed in this review.
Keywords: anti-diabetic treatment